Penerapan Nilai-Nilai Qur’ani dalam Pembelajaran PAI di SMP Ikhlasiyah Palembang (Indo-MathEdu Intellectuals Journal, 2023)
This research is titled "Application of Qur'anic Values in Islamic Education Learning at SMP Ikhlasiyah Palembang." This study uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. Data analysis was conducted through stages of collection, presentation, verification, and conclusion drawing. The results of the research show that the application of Qur'anic values in Islamic Education learning at SMP Ikhlasiyah Palembang has been well-implemented, covering activities such as instilling faith values, applying noble moral values, and maintaining discipline in the educational process. The school has an excellent educational program for instilling faith values in students, so they not only understand Islamic teachings theoretically but also can apply them in daily life. Other school programs conducted with a holistic and consistent approach are also effective in instilling noble morals in students, helping them become responsible individuals, empathetic, and able to contribute positively to society. The application of Qur'anic values in Islamic Education learning involves discipline in the learning process through various methods such as reading and interpreting the Qur'an, group discussions, project assignments, and examples from the life of Prophet Muhammad SAW and his companions